Teachers-to-be and Islam. Has a change taken place? - Lendzion, Joanna (Zakład Edukacji Międzykulturowej i Badań nad Wsparciem Społecznym Wydziału Nauk Historycznych i Pedagogicznych Uniwersytetu Wrocławskiego, 2017)
The article contains a comparative analysis of the diagnostic survey results (in conjunction with the verbal fluency tool) conducted twice (June 2015 and 2016) among Jan Kochanowski University’s students, BA undergraduates, major of studies – pedagogics.
Keywords: Islam; Islamophobia; knowledge; multiculturalism; teacher; tolerance